Implementation of Principal Academic Supervision as a Strategy for Improving Teacher Performance in Elementary Schools - Setyawan Ning Hutama; Dwi Ismawati; Nur Baity Wahidatun; Soedjono Soedjono (Journal of Innovation and Research in Primary Education, 2026)
Academic supervision is widely recognized as a strategic mechanism for improving instructional quality in primary schools; however, studies that emphasize a humanistic and collaborative supervision model within the implementation of the Merdeka Curriculum remain limited. This study aims to examine the implementation of academic supervision by the principal and its contribution to improving teachers’ professional competence and learning quality at SD Pedurungan Kidul 05. Using a qualitative descriptive design, the study explored supervision practices as they naturally occurred in the school context. Data were collected through in-depth interviews, classroom observations, and document analysis involving the principal, classroom teachers, and educational staff. Data analysis followed the interactive model of Miles and Huberman, while credibility was ensured through triangulation of sources and methods. The findings reveal that academic supervision was implemented systematically through pre-observation, classroom observation, and post-observation stages, applying a humanistic and collaborative approach. This supervision model positioned teachers as professional partners, encouraging reflective teaching and continuous improvement. As a result, teachers showed notable improvements in lesson planning, differentiated instructional strategies, classroom management, and formative assessment practices aligned with the Merdeka Curriculum. These changes contributed to more student-centered learning and increased student engagement. This study offers empirical evidence that humanistic academic supervision strengthens instructional practices and supports sustainable learning quality improvement in primary education.